(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of using flannel board syllable cards on the early reading skills of first-grade students at SDN Paninggaran, Kuningan Regency. Reading skills are basic abilities that involve thinking processes, symbol recognition, and meaning comprehension, which play an important role in the development of children’s literacy skills from an early age. This study used an experimental method with a one-group pretest-posttest design. The independent variable in this study was flannel board syllable cards, while the dependent variable was early reading skills. The research subjects consisted of 21 first-grade students at SDN Paninggaran, who were selected using total sampling. Data were collected through reading tests before and after the treatment. Data analysis was performed using a t-test to determine the difference between the pretest and posttest results. The results showed that there was a significant effect of using flannel board syllable cards on improving students’ early reading skills, with a t-value of 9.61 greater than the t-table value of 2.06. These findings indicate that the use of flannel board syllable cards is effective in helping students recognise syllables, improve reading fluency, and foster an interest in learning to read from an early stage.